Radiotherapy and chemotherapy for inoperable non-small cell lung cancer. Issue 837 (July 1995) - Bleasdale, C.; Jones, B.
Abstract : Non-small cell lung cancer is a major cause of mortality and significant morbidity in the UK. The majority of patients are inoperable and the optimum management of these patients requires a multidisciplinary approach involving the cooperation of respiratory physicians, thoracic surgeons and clinical oncologists (radiotherapists). Treatment techniques are constantly being refined and new approaches developed.